2018
DOI: 10.1073/pnas.1712107115
|View full text |Cite
|
Sign up to set email alerts
|

Tim-3 co-stimulation promotes short-lived effector T cells, restricts memory precursors, and is dispensable for T cell exhaustion

Abstract: Tim-3 is highly expressed on a subset of T cells during T cell exhaustion in settings of chronic viral infection and tumors. Using lymphocytic choriomeningitis virus (LCMV) Clone 13, a model for chronic infection, we found that Tim-3 was neither necessary nor sufficient for the development of T cell exhaustion. Nonetheless, expression of Tim-3 was sufficient to drive resistance to PD-L1 blockade therapy during chronic infection. Strikingly, expression of Tim-3 promoted the development of short-lived effector T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
136
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(150 citation statements)
references
References 39 publications
13
136
1
Order By: Relevance
“…AICD has also been described to be a major cause of T cell depletion in other chronic infections, such as HIV 48,49 , independent of direct cytotoxic effects of the virus itself. Intriguingly, Tim-3 and Lag-3 also appear to be dispensable for the development of T cell exhaustion, as Tim-3 KO and Lag-3 KO mice were demonstrated to harbor fewer antigen-specific T cells and do not control virus replication after challenge with chronic LCMV clone 13 50,51 . In contrast, PD-1/PD-L1 blockade during chronic viral infections restores the function of exhausted CD8 + T cells, in particular antigen-specific cells, and results in enhanced T cell responses and virus control in different virus models 8,52,53 , which suggests that these two molecules operate through distinct pathways to dampen immune cell responses and might thus partake in different physiological processes, where immune suppression is required.…”
Section: Discussionmentioning
confidence: 99%
“…AICD has also been described to be a major cause of T cell depletion in other chronic infections, such as HIV 48,49 , independent of direct cytotoxic effects of the virus itself. Intriguingly, Tim-3 and Lag-3 also appear to be dispensable for the development of T cell exhaustion, as Tim-3 KO and Lag-3 KO mice were demonstrated to harbor fewer antigen-specific T cells and do not control virus replication after challenge with chronic LCMV clone 13 50,51 . In contrast, PD-1/PD-L1 blockade during chronic viral infections restores the function of exhausted CD8 + T cells, in particular antigen-specific cells, and results in enhanced T cell responses and virus control in different virus models 8,52,53 , which suggests that these two molecules operate through distinct pathways to dampen immune cell responses and might thus partake in different physiological processes, where immune suppression is required.…”
Section: Discussionmentioning
confidence: 99%
“…Second, at least four ligands have been described to interact with Tim-3, including galectin-9, phosphatidylserine (PS), HMGB1 and CEACAM1 (7)(8)(9), which are known to also interact with other and distinct receptors (15,(17)(18)(19)(20), making the definition of important receptor-ligand interactions difficult at best. Third, studies from multiple labs on both T cells and non-T cells have directly or indirectly demonstrated an ability of Tim-3 to transmit positive, activationpromoting, signals (21)(22)(23)(24)(25)(26). Our own work has suggested a model by which expression of Tim-3 might either promote the development of T cell exhaustion by enhancing or sustaining TCR signaling or actually represent a "last-ditch" effort by exhausted T cells to maintain some function (22,27).…”
Section: Introductionmentioning
confidence: 95%
“…We mixed Jurkat T cells expressing either the CD28-or Tim3containing CAR with Raji B cells (CD20+) as targets. Given our previous findings (above and (22,24)) that Tim-3 is capable of co-stimulating TCR-mediated phosphorylation of the ribosomal S6 protein, we determined whether this activity is retained in the Tim-3 CAR. Indeed, consistent with our functional data, the Tim-3 CAR mediated robust pS6 upregulation, similar to the function of the CD28 CAR, in both Jurkat T cells (not shown) and primary human T cells (Fig.…”
Section: Enforced Is Localization Of the Tim-3 Cytoplasmic Tail Is Stmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, reduced expression of CEACAM1 and TIM-3 on circulating CD4 + and CD8 + T lymphocytes in individuals with multiple sclerosis correlates with disinhibited T cell activation and consequently increased disease severity [132]. TIM-3 has been suggested to also possess activating functionality [133][134][135][136][137][138][139][140][141]. This raises the possibility that CEACAM1 associates with TIM-3 as it does other activating receptors and serves to inhibit its function or that CEACAM1 association with TIM-3 enables other novel inhibitory signaling mechanisms that remain to be determined.…”
Section: Ceacam1 Regulates T Cell Activation and Mediates Tolerance-mentioning
confidence: 99%